Lobbying the executives: differences in lobbying patterns between elected politicians, partisan advisors and public servants - Cooper, Christopher A.; Boucher, Maxime (Frontiers in Political Science, 2024)
Research from parliamentary countries suggests that lobbyists tend to focus their attention on public office holders within the executive government more than those within the legislative branch. To date, however, research studying executive-lobbying relations tends to treat “the executive” and “lobbyists” as two homogenous groups. Yet importantly, not all executive personnel and lobbyists are the same. The executive is made-up of popularly elected politicians, partisan advisors and non-partisan bureaucrats, who vary in their skills, motivations, responsibilities and power within government. Differences also exist in the level of expertise and political representativeness between in-house and consultant lobbyists. Using longitudinal data between 2015 and 2022 from Canada's Lobbyist Registry, this article digs deeper into the executive-lobbying nexus by examining the number of contacts consultant and in-house lobbyists have with different executive personnel—ministers, partisan advisors, senior public servants and non-senior public servants. Although the data shows no meaningful variation tied to differences across partisan-political and administrative personnel within the executive, there is substantive variation in lobbying intensity between upper and lower ranked executive personnel; in-house lobbyists lobby senior political and senior administrative personnel twice as much as consultant lobbyists. These findings are consistent with theory on the expertise and representative function some lobbyists possess, more so than theory emphasizing differences between partisan-political and administrative personnel within the executive.